The Joint Vasculitis Registry in German-speaking countries (GeVas) – a prospective, multicenter registry for the follow-up of long-term outcomes in vasculitis - Iking-Konert, Christof; Wallmeier, Pia; Arnold, Sabrina; Adler, Sabine; Groot, Kirsten de 1964-; Hellmich, Bernhard 1968-; Hoyer, Bimba Franziska 1977-; Holl-Ulrich, Konstanze; Ihorst, Gabriele; Kaufmann, Margit; Kötter, Ina 1962-; Müller-Ladner, Ulf 1964-; et al. (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2022)
Abstract: Background Vasculitides comprise a group of rare diseases which affect less than 5 in 10.000 individuals. Most types of vasculitis can become organ- and life-threatening and are characterized by chronicity, high morbidity and relapses, altogether resulting in significant morbidity and mortality. Previous studies have been either monocentric or mainly retrospective – studies with a prospective design mostly consisted of rather small cohorts of 100 to 200 patients. The aim of the Joint Vasculitis Registry in German-speaking countries (GeVas) is to record all patients who have been recently diagnosed with vasculitis or who have changed their treatment due to a relapse (inception cohort). In GeVas, data are collected prospectively in a multicenter design in Germany, Austria and Switzerland. By this approach, courses of vasculitis and their outcomes can be monitored over an extended period. Methods GeVas is a prospective, web-based, multicenter, clinician-driven registry for the documentation of organ manifestations, damage, long-term progress and other outcomes of various types of vasculitis. The registry started recruiting in June 2019. As of October 2020, 14 centers have been initiated and started recruiting patients in Germany. Involvement of sites in Austria and the German-speaking counties of Switzerland is scheduled in the near future. Discussion In June 2019, we successfully established a prospective multicenter vasculitis registry being the first of its kind in German-speaking countries. The participating centers are currently recruiting, and systematic analysis of long-term vasculitis outcomes is expected in the ensuing period. Trial registration German Clinical Trials Register (Deutsches Register Klinischer Studien): DRKS00011866. Registered 10 May 2019